2007
DOI: 10.1517/13543776.17.8.927
|View full text |Cite
|
Sign up to set email alerts
|

Antiparasitic activity of aromatic diamidines and their patented literature

Abstract: Aromatic diamidines and related compounds are DNA minor groove-binding binders that display excellent antimicrobial activity towards bacteria, fungi and protozoa. This review focuses on the activity and patented information related to aromatic diamidines (and analogs) towards four relevant parasitic protozoa, African and American trypanosomas, Leishmania and Plasmodium, which are parasites that still cause incurable neglected diseases annually killing millions of people in many developing countries. The overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 90 publications
0
7
0
Order By: Relevance
“…AD and their congeners present broadspectrum activity against pathogenic microorganisms, and some of them have veterinary and human clinical uses {e.g., pentamidine isethionate [1,5-bis(4-amidino-phenoxy)pentane] (Pentacarinat; Rhodia)} (45,57,72). However, these compounds often cause considerable side effects and require parenteral routes of administration, which stimulates the synthesis and screening of new analogs and prodrugs to overcome these limitations (19,34,56,59).…”
mentioning
confidence: 99%
“…AD and their congeners present broadspectrum activity against pathogenic microorganisms, and some of them have veterinary and human clinical uses {e.g., pentamidine isethionate [1,5-bis(4-amidino-phenoxy)pentane] (Pentacarinat; Rhodia)} (45,57,72). However, these compounds often cause considerable side effects and require parenteral routes of administration, which stimulates the synthesis and screening of new analogs and prodrugs to overcome these limitations (19,34,56,59).…”
mentioning
confidence: 99%
“…To overcome these limitations, new aromatic dications and their prodrugs have been synthesized and screened both in vitro and in vivo against different pathogens (2,26). Recent studies have shown good in vitro and in vivo activity for diamidines such as furamidine (DB75), its N-phenyl-substituted analogue (DB569), and reversed amidines (5,7,8,23,24) against T. cruzi.…”
mentioning
confidence: 99%
“…Supplementary crystallographic data have been deposited with the Cambridge Crystallographic Data Centre, CCDC nos. 1031758 (1), 1031757 (2), 1031756 (3), 1031755 (4), 1031753 (5a), 1031754 (5b), 1031752 (6), 1031750 (7), 1031749 (8), 1031748 (9), 1031747 (10). Copies of the data may be obtained free of charge from The Director, CCDC, 12 Union Road, Cambridge CB2 1EZ, UK (fax: +44-1223-336033; e-mail: deposit@ccdc.cam.ac.uk or www: http://www.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Due to the similarity of the amidine group to the guanidine group of L-arginine, amidines can interact with the L-arginine binding site of NO synthase. 8 Several benzamidine derivatives are potent competitive inhibitors of trypsin-and trypsin-like enzymes and serineproteases.…”
Section: Introductionmentioning
confidence: 99%